2020
DOI: 10.1021/acsomega.0c01655
|View full text |Cite
|
Sign up to set email alerts
|

A Copper(II) Macrocycle Complex for Sensing Biologically Relevant Organic Anions in a Competitive Fluorescence Assay: Oxalate Sensor or Urate Sensor?

Abstract: Fluorescence sensing of oxalate has garnered some attention in the past two decades as a result of this anion’s prominence and impact on society. Previous work on oxalate sensors and other divalent anion sensors has led to the conclusion that the sensors are selective for the anion under investigation. However, sensor selectivity is often determined by testing against a relatively small array of “guest” molecules or analytes and studies often exclude potentially interfering compounds. For example, studies on o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…found a better fit with a 1 : 2 binding model than a 1 : 1 bindng model. [38] Under the identical conditions, the association constants of 1⋅EY were determined for other anions were consistent with a 1 : 2 binding model. [59] The overall binding constants (in log K) and their corresponding free energies (À ΔG o ) are listed in Table 2.…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…found a better fit with a 1 : 2 binding model than a 1 : 1 bindng model. [38] Under the identical conditions, the association constants of 1⋅EY were determined for other anions were consistent with a 1 : 2 binding model. [59] The overall binding constants (in log K) and their corresponding free energies (À ΔG o ) are listed in Table 2.…”
Section: Introductionsupporting
confidence: 59%
“…[27][28] Using a supramolecular approach, there has been an immense interest in developing efficient chemical sensors for oxalate by colorimetric and fluorescence methods. [29][30][31][32][33][34][35][36][37][38][39][40][41] Previous studies demonstrated that the complexes of certain metal ions including zinc, [32][33] copper, [34][35][36][37][38][39] nickel, [40][41] and calcium [42] can be used as suitable chemosensors for detecting an oxalate anion in solution.…”
Section: Introductionmentioning
confidence: 99%
“…There is substantial interest in developing indicator-displacement-based methods for detecting oxalate that do not require enzymes, liquid chromatography, or mass spectrometry. Many of these methods quantify fluorescence quenching, or, more often, gain of fluorescence upon addition of the analyte [36]. The principle of operation is shown in Fig.…”
Section: Indicator Displacement-based Uv Colorimetric and Fluorescenc...mentioning
confidence: 99%
“…A recent report by Hontz et al revisited a fluorescence-based indicator displacement method, clearly demonstrating that interference from untested compounds in biological samples may be more prevalent than is sometimes suggested [36]. Specifically, it was shown that a dinuclear copper(II)-based macrocycle with the ability to quench eosin Y fluorescence, although reported as oxalate selective, exhibited a stronger response to citrate and oxaloacetate.…”
Section: Indicator Displacement-based Uv Colorimetric and Fluorescenc...mentioning
confidence: 99%
“…Anion binding and the concomitant release of eyosin Y was signalled by an increase in the characteristic fluorescence of the free dye. [82][83][84][85][86][87][88] In a twist on the indicator-displacement method, Zhang and co-workers synthesised a host a 2-(hydroxy)-naphthyl imino-functionalised pillar [5]arene 51 (Fig. 27), which coordinated to Fe(III) through its imine nitrogen and hydroxyl groups in H 2 O/DMSO (1 : 9, v/v).…”
Section: Organic and Biomolecular Chemistry Reviewmentioning
confidence: 99%